Age-related reference intervals for ambulatory electrocardiographic parameters in healthy individuals - Hashimoto, Kenichi; Harada, Naomi; Kimata, Motohiro; Kawamura, Yusuke; Fujita, Naoya; Sekizawa, Akinori; Ono, Yosuke; Obuchi, Yasuhiro; Takayama, Tadateru; Kasamaki, Yuji; Tanaka, Yuji (Frontiers in Cardiovascular Medicine, 2023)
Background The advent of novel monitoring technologies has dramatically increased the use of ambulatory electrocardiography (AECG) devices. However, few studies have conducted detailed large-scale investigations on the incidence of arrhythmias over 24 h, especially ectopy, in healthy individuals over a wide age range. Objectives This study aimed to investigate the incidence of arrhythmias detected using AECG and associated factors, in healthy individuals, over a wide age range. Methods In this cross-sectional study, we performed AECG on 365 healthy volunteers (median [interquartile range]: 48 [36, 67], 20–89 years, 165 men) under free-running conditions for 24 h. Ultrasonic echocardiography and heart rate variability analysis were performed to explore the factors associated with the incidence of arrhythmias. Results The 97.5th percentile of single ventricular ectopy (VE) was 149/day, 254/day, and 1,682/day in the 20–39-, 40–59- and 60–89-year age groups, respectively; that of single supraventricular ectopy (SVE) was 131/day, 232/day, and 1,063/day, respectively. Multivariate analysis revealed that aging was the only independent significant factor influencing the frequency of VE (β = 0.207, P = 0.001). Age (β = 0.642, P < 0.001), body mass index (BMI) (β = −0.112, P = 0.009), and the root mean square of successive differences in RR intervals (β = 0.097, P = 0.035) were factors significantly associated with SVE frequency. Conclusions Age-specific reference intervals of VE and SVE in a large population of healthy participants over a wide age range were generated. VE and SVE increased with age; SVE was influenced by BMI and the aging-induced decrease in parasympathetic tone activity.